Protection of human rights as one of the guarantees in criminal proceedings. (Journal of actual problems of jurisprudence, 2016)
In this article the author examines one of the main tasks of the criminal proceedings to ensure individual rights. The author reveals the contemporary and historical concepts in the protection of human rights in criminal proceedings. The article outlines the main principles of individual rights in criminal proceedings.
Keywords: criminal proceedings; proof theory; solve the crime; the suspect; a fact